Risk Factors for Acute Respiratory Tract Infections in Young Greenlandic Children - Koch, Anders; Mølbak, Kåre; Homøe, Preben; Sørensen, Per; Hjuler, Thomas; Olesen, Mette Ehmer; Pejl, June; Pedersen, Freddy Karup; Olsen, Ove Rosing; Melbye, Mads (American Journal of Epidemiology, 2003)
Acute respiratory infections cause considerable morbidity among Inuit children, but there is very little information on the risk factors for these infections in this population. To identify such factors, the authors performed a prospective community-based study of acute respiratory infections in an open cohort of 288 children aged 0–2 years in the town of Sisimiut, Greenland. Between July 1996 and August 1998, children were monitored weekly, and episodes of upper and lower respiratory tract infections were registered. Risk factor analyses were carried out using a multivariate Poisson regression model adjusted for age. Risk factors for upper respiratory tract infections included attending a child-care center (relative risk = 1.7 compared with home care) and sharing a bedroom with adults (relative risk = 2.5 for one adult and 3.1 for two adults). Risk factors for lower respiratory tract infections included being a boy (relative risk = 1.5), attending a child-care center (relative risk = 3.3), exposure to passive smoking (relative risk = 2.1), and sharing a bedroom with children aged 0–5 years (relative risk = 2.0 for two other children). Breastfeeding tended to be protective for lower respiratory tract infections. The population-attributable risk of lower respiratory tract infections associated with passive smoking and child-care centers was 47% and 48%, respectively. The incidence of acute respiratory infections among Inuit children may be reduced substantially through public health measures.